Implementación de una máquina mezcladora para balanceado en la microempresa avícola san Nicolás ubicada en la parroquia san buenaventura - Analuisa Escobar, Crhistian Gonzalo (2018)
The present work is focused on helping the micro-company "San Nicolás" in the design and construction of the mixing machine for the elaboration of balancing for birds, since this activity was carried out manually, which involved having a person dedicated exclusively to this activity for long periods of time; one of the main reasons why this research was proposed to reduce the mixing time, for this a maximum capacity of 500 kg. was considered. With this information about different kinds of blenders in the market were investigated; selecting the helical screw mixer as it is the best suited to mix granulated powders. The machine is constituted by the feeding system and the mixer. The loading system is where the raw material enters to be mixed while the mixing system is formed by an axis coupled by two helicoidally screws baroladas in circular and left-handed that facilitates the transport of the material and the mixture. This system is supported on two chains with bearings called wall bearings. The power transmission system of the mixer consists of a 5HP motor coupled directly to a 3-inch pulley and aligned to a 4-inch pulley attached to the speed reducer through two tensioning bands. A 12-tooth sprocket is connected to the output channel of the speed reducer that connects to another 40-tooth sprocket through a transmission chain, which is attached to the transmission tube that supports the propellers that cause the product to be mixed at a constant speed (30 rpm) that is obtained from the speed reducer. After the machine was implemented, "ash" laboratory tests were carried out to guarantee the homogeneity of the product obtained; the results of the tests determined that after 3 minutes a homogeneous mixture is obtained in the balanced.